Visual and Verbal Communication in Coldplay’s Music Video Clip “Hymn for the Weekend” - Hanif Putra, Viqi (Humanis, 2018)
The title of the study is “Visual and Verbal Communication in Coldplay’s Music Video Clip Hymn for the Weekend”. The study is commonly aimed at finding out the messages from the lyrics of the song music video clip. The data analysis were collected by documentation method and note taking technique by listening to the song and analyzing the meaning of the word in song lyrics based onVisual Communication Elements theory proposed by Dyer (1993) and the theory of meaning by Geoffrey Leech (1974). The findings of the current study show that there are six categories from the visual communication elements including appearance, manner, activity, props, settings, and images, as well as the meaning found in this study were connotative meaning, conceptual meaning, stylistic meaning, and affective meaning.